2017
DOI: 10.1590/1807-1929/agriambi.v21n10p721-725
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of the foam-mat drying curves of guava pulp

Abstract: A B S T R A C TIn foam-mat drying, the liquid food is foamed by the addition of a foaming agent, for example, albumin. The aim of this study was to evaluate the adjustment of mathematical models to foam mat drying curves of guava pulp. The fits were evaluated using samples with 4 and 8% albumin (m m -1 ) and drying temperatures of 75, 80 and 85 °C. The samples were placed on aluminum trays. Drying was carried out in a tray dryer. The Lewis, Page, Midilli and Logarithmic models were fitted to the experimental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 17 publications
4
10
0
2
Order By: Relevance
“…These results are in agreement with those reported by Chaux‐Gutiérrez et al. (2017) in mango foam mat drying, Maciel, Afonso, Costa, Severo, and Lima (2017) for guava, and Dehghannya et al. (2018a) for lime juice.…”
Section: Resultssupporting
confidence: 92%
“…These results are in agreement with those reported by Chaux‐Gutiérrez et al. (2017) in mango foam mat drying, Maciel, Afonso, Costa, Severo, and Lima (2017) for guava, and Dehghannya et al. (2018a) for lime juice.…”
Section: Resultssupporting
confidence: 92%
“…In addition, the Midilli et al model could adequately describe the drying curves of apple under the picked experimental conditions. The findings of this study are in agreement with former findings proclaimed in the drying of pulped coffee (Coradi et al 2017), guava pulp (Maciel et al 2017), and apricot halves (Kayran & Doymaz 2017) for Midilli et al model.…”
Section: Drying Kinetics Of Applesupporting
confidence: 93%
“…moisture content reduces with a decrease in egg albumen concentration but increases with increases in carboxyl methylcellulose concentration. Maciel et al [15] also reported that moisture loss was faster in samples containing higher albumen concentration.…”
Section: Optimization Of Drying Characteristics Of Watermelon Pulpmentioning
confidence: 93%